1973
DOI: 10.1037/h0033943
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward homosexuality: Preservation of sex morality or the double standard?

Abstract: Just as there is now a shift in emphasis in regard to other minority groups (e.g., the nonpoor are being studied in order to make possible needed and desired changes for the poor; Mac-Donald, 1973), the time is perhaps right to study the sources of the nonhomosexual's attitudes toward homosexuality.Despite repeated negative findings, researchers continue to look for data to substantiate the belief that homosexuals are abnormal. The explanation for such persistance may lie more in the nature, needs, and values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 3 publications
0
32
1
Order By: Relevance
“…Herek (1984) questioned the necessity of multifactorial scales, and ultimately concluded that only a single factor was required to conceptualize heterosexism. Herek (1984) reported four studies which drew on both earlier attitude measures (Levitt & Klassen, 1974;MacDonald et al, 1973;Millham et al, 1976;Smith, 1971) and some original items. Notably, Herek excluded items from Mosher and O'Grady (1979) arguing that the "locker room" language of these behavioral items would offend participants instead of tapping into feelings of personal threat.…”
Section: Measuring Anti-homosexual Prejudice Ii: Social Reform and MImentioning
confidence: 99%
“…Herek (1984) questioned the necessity of multifactorial scales, and ultimately concluded that only a single factor was required to conceptualize heterosexism. Herek (1984) reported four studies which drew on both earlier attitude measures (Levitt & Klassen, 1974;MacDonald et al, 1973;Millham et al, 1976;Smith, 1971) and some original items. Notably, Herek excluded items from Mosher and O'Grady (1979) arguing that the "locker room" language of these behavioral items would offend participants instead of tapping into feelings of personal threat.…”
Section: Measuring Anti-homosexual Prejudice Ii: Social Reform and MImentioning
confidence: 99%
“…Traditional genderroles are shared beliefs, attitudes and behaviors that define hegemonic masculinity and femininity (e.g., Eagly, 1987;Zucker, 2001) and characterize a gender ideological system that supports a double standard for the sexes (MacDonald, Huggins, Young, & Swanson, 1973). A man learns to be different from women and similar to other men in order to become a 'real man', and a woman learns to be different from men and similar to other women in order to become a 'real woman'.…”
Section: Palabras Clave: Rol De Género Prejuicio Sexual Diferenciacmentioning
confidence: 99%
“…Rather than focusing on the "etiology" and "cure" of homosexuality, theorists and researchers in psychology began to suggest that negative attitudes toward homosexuals, rather than homosexuality itself, are the cause of many of the difficulties that homosexuals face (Smith, 1971). Many of these researchers rejected what they referred to as the "victim analysis," which focused on the homosexual, and redirected their empirical pursuits toward the possible victimizers and, more specifically, toward the attitudes of nonhomosexuals toward homosexuals and homosexuality (MacDonald, Huggins, Young, & Swanson, 1972). Homosexuality was now taken to be a normal, healthy, life-style choice, and thus a new question arose: What are the etiology of, associated features of, and cure for individuals who have negative attitudes and reactions toward homosexuals and homosexuality?…”
Section: A Brief Historymentioning
confidence: 96%